Bone loss in diabetic patients with chronic kidney disease - Rigalleau, V.; Lasseur, C.; Raffaitin, C.; Perlemoine, C.; Barthe, N.; Chauveau, P.; Aparicio, M.; Combe, C.; Gin, H. (Diabetic medicine, 2007)
Objective  We investigated whether loss of bone is detectable during follow‐up of diabetic patients with chronic kidney disease (CKD). Research design and methods  In 40 initially non‐dialysed diabetic patients with CKD (isotopic glomerular filtration rate < 60 ml/min/1.73 m2 or albumin excretion rate > 30 mg/24 h), body composition (DEXA scan) and glomerular filtration rate (GFR determined from 51Cr‐EDTA clearance) were measured at a 2‐year interval, and compared by paired t‐tests. Results  The 40 patients, mainly with Type 2 diabetes (n = 28), were men (n = 28), aged 65 ± 11 years, with diabetes duration 18 ± 11 years. GFR was initially 38.0 (range 8–89) ml/min/1.73 m2. CKD progressed during follow‐up: eight started haemodialysis and GFR declined in the 32 others (P < 0.05 vs. initial). T‐scores for total body (initial −0.61 ± 1.11, final −1.11 ± 1.40; P < 0.001) and femoral neck (initial −1.88 ± 0.15, final −2.07 ± 0.15; P < 0.05) declined. Ten patients were osteopaenic at baseline (no osteoporosis), whereas most were osteopaenic (n = 21, P < 0.05) and five were osteoporotic at final assessment. The 16 patients who became osteopaenic or osteoporotic during follow‐up did not differ from the others for the type of diabetes, age, GFR, albumin excretion rate, HbA1c, GFR reduction and the requirement for dialysis during follow‐up. They were all men (P < 0.01 by chi‐squared test), with reduced initial total body T‐score (−1.20 ± 0.82, others −0.32 ± 1.13; P < 0.05) and a lower body mass index (24.6 ± 4.3; others 27.7 ± 4.3; P < 0.05). Conclusion  Bone loss, especially in the femoral neck, is progressive in diabetic patients with CKD.